PENINGKATAN EKONOMI KREATIF DIGITAL MARKETING MELALUI USAHA MIKRO, KECIL, DAN MENENGAH (UMKM) PEPES IKAN DESA LINGSAR KECAMATAN LINGSAR KABUPATEN LOMBOK BARAT - Putri, Baiq Alisa Nakita; Syafatullah, Aqsal Ilham; Wirayuda, Hasan; Putra, Made Krisna Suryana; Syuqroni, Muhammad; Tokan, Stefania Lorensa Ina; Putri, Enisa Padila; Prastiwi, Rizky Wahyu; Pujiarti, Ayu; Purnamasari, Iga Larashati; Zahra, Siti Astiti; Bulkaini (Universitas Mataram, 2025)
MSMEs play a vital role in economic growth, yet they still face challenges in digital marketing. The objective of the University of Mataram Community Service Program in Lingsar Village (July to August 2025) was to help small and medium-sized enterprises (SMEs) producing pepes ikan (fish pepes) improve their capabilities through digital marketing assistance. Qualitative analysis using observation, interviews, and surveys was used. The objectives were (1) to promote the creation of QRIS DANA for cashless transactions, (2) to produce videos promoting pepes ikan on social media, and (3) to organize the infrastructure of the business area. This program successfully encouraged MSMEs in Lingsar Village to use digital technology, expand their market, and enhance their branding.